Influence of doping concentration on the performances of multi-junction solar cell InGaP/InGaAs/Ge - Djeriouat, Khadidja; Kerai, Salim; Ghaffour, Kheireddine (Institute of Advanced Engineering and Science, 2026)
Recently, because of the high costs of experimentation, researchers have turned to simulation. This type of simulation makes it possible to determine, at any point in the volume of a component, the densities of carriers, electrons and holes, the energies, the recombination rates, the electric fields and other parameters that can be deduced from it, such as currents and voltages. Our paper presents the simulation results of the heterojunction solar cell made of GaInP/GaInAs/Ge materials using Silvaco's Atlas software to optimize its electrical efficiency by acting on the doping of photoactive layers. We have chosen a tandem structure when the top cell is constructed by Ga0.4In0.6P, in the middle cell, we used Ga0.1In0.9As and the bottom cell is formed by germanium (Ge). The simulation is performed under the following conditions: 1-sun (0.1 w/cm2), AM1.5G illumination and at temperature 300 K. We obtained an efficiency of 24.65%.